Infinitely Many Solutions for a Semilinear Elliptic Equation with Sign-Changing Potential. (16th June 2009) - Yu, Chen; Yongqing, Li
Abstract : We consider a similinear elliptic equation with sign-changing potential− Δ u − V ( x ) u = f ( x, u ), u ∈ H 1 ( ℝ N ), whereV ( x ) is a function possibly changing sign inℝ N . Under certain assumptions onf, we prove that the equation has infinitely many solutions.